Investigación sobre la transición entre las doctrinas mercantilistas y el nacimiento de la Economía Política. Un análisis de los aportes de Thomas Mun, James Steaurt y David Hume (2017)
In this article we study the progression of economic thought of the 17th and 18th centuries, based on the analysis of original emblematic works of the period such as Thomas Mun, James Steuart and David Hume. It is investigated how these authors begin to reveal the fragmentary and limited character of the conceptions elaborated by the mercantilist doctrines on the economic processes before the emergency and the development of industrial capitalism. It also examines how, in this context, the efforts of these economic doctrines of the eighteenth century arise from the understanding of economic processes in a universal and not unilaterally national context, striving to strengthen the formation of a unified theoretical body of the capitalist system as a whole, giving way to Political Economy.